PENYULUHAN DAN PENDAMPINGAN PENGOLAHAN KEARIFAN LOKAL IKAN BANDENG TARAKAN SEBAGAI UPAYA PENANGANAN STUNTING PADA BALITA - Nurul Hidayatun Jalilah; Agus Purnama Sari (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Community empowerment in communities affected by covid_19, especially housewives who have stunted toddlers provides its own color for business development that leads to the utilization of milkfish which is processed into various variants in line with the development of technological innovation in the culinary field of society. The methods used are outreach, training and mentoring, monitoring, and evaluation. The training participants were housewives from Gunung Lingkas Village, Tarakan City. The results achieved are that the processing of milkfish is a representative form of changing the paradigm of society in utilizing milkfish which has been processed traditionally with existing local ingredients, then switches to modern processing using modern technology to give the taste and tastes of service users who are passionate about Modern processed foods such as Milkfish Presto, Shredded Milkfish, Milkfish Sticks and Milkfish Crackers. "Through training on processing milkfish products with various and innovative variants" which has been organized by the Community Service Team at the University of Borneo, it is hoped that it can increase knowledge and skills for housewives to be able to process milkfish in a more innovative and modern way to increase entrepreneurial activity and income among them. The training participants were very enthusiastic about participating in these activities and the participants had great hopes that community service activities such as milkfish processing training could be carried out on an ongoing basis and by providing various materials to increase their knowledge and skills towards a prosperous society in the future